Impact of Monetary Policy Shocks in the Peruvian Economy Over Time - Perez Rojo, Flavio Fernando (2024)
We investigate the evolution of the impact of monetary policy (MP) shocks in Peru in 1996Q1-2018Q2 using a set of time-varying parameter vector autoregressive models with stochastic volatility (TVP-VAR-SV), as proposed by Chan and Eisenstat (2018). The main results are: (i) the volatilities, intercepts, and contemporaneous coefficients change more gradually than VAR coefficients over time; (ii) the volatility of MP shocks falls from 4% to 0.3% on average during the Inflation Targeting (IT) regime; (iii) in the long run, a contractionary MP shock decreases both gross domestic product (GDP) growth and inflation by 0.28% and 0.1%, respectively; (iv) the interest rate reacts faster to aggregate supply shocks than to both aggregate demand shocks and exchange rate shocks; (v) under the pre-IT regime, MP shocks explain almost 20%, 10%, and 85% of the uncertainty in GDP growth, inflation, and the interest rate, respectively; and under the IT regime, all these percentages shrink to 1-2%. The sensitivity analysis confirms the robustness of the main results across various prior specifications, measures of external and domestic variables, and recursive identifications. In general, the results show that MP has contributed to diminishing macroeconomic volatility in Peru.